POTENTIAL OF MYCORRHIZAL INOCULATION AND CATTLE RUMEN DIGESTA IN THE BIOREMEDIATION OF SPENT ENGINE OIL CONTAMINATED SOIL - E NKEREUWEM, MICHAEL; ADELEYE, ADENIYI O; KAMALDEEN, FATIMAH; SOWUNMI, LINDA I; IJAH, CHRISTIANA J; NZAMOUHE, MAXIMILLIEN; BASHIR, MUSBAHU; LEMUEL, ASIMYA (Innovare Journal of Sciences, 2024)
Soil pollution by crude oil contamination has become a major constraint on agricultural productivity. Physicochemical techniques are often expensive. However, bioremediation of petroleum hydrocarbon polluted soil is cost-effective. Therefore, the study was carried out to analyze the influence of mycorrhiza and cattle rumen digesta on bioremediation of Spent Engine Oil (SEO) contaminated soil in Dutse, Jigawa state. Soil samples were randomly collected from the University Research and Teaching Farm. About 2.5 kg of sterilized topsoil (0–15 cm) was filled into pots and arranged in a 2×2×3 factorial experiment in completely randomized design with three replications. Mycorrhiza and cattle rumen digesta were at two levels, while SEO was at three levels. Data were collected on the total petroleum hydrocarbon (TPH) content, bacterial and fungal colony count. Data were analyzed using ANOVA at α 0.05. Results obtained from the study show that mycorrhiza and cattle rumen digesta increased the colonies of fungi and bacteria resulting in significantly enhanced TPH degradation in the contaminated soil. However, cattle rumen digesta significantly (p<0.05) enhanced TPH degradation, bacterial and fungal population the most compared to mycorrhiza alone. Combined cattle rumen digesta and mycorrhiza application resulted in significantly (p<0.05) lower residual TPH content in the contaminated soil compared to using cattle rumen digesta or mycorrhiza alone. Thus, cattle rumen digesta and mycorrhiza should be used in bioremediation of petroleum hydrocarbon impacted soils.